CD30 receptor-targeted lentiviral vectors for human induced pluripotent stem cell-specific gene modification - Friedel, Thorsten; Jung-Klawitter, Sabine; Sebe, Attila; Schenk, Franziska; Modlich, Ute; Ivics, Zoltán; Schumann, Gerald G.; Buchholz, Christian J.; Schneider, Irene C. (Stem Cells and Development, 2016)
Cultures of induced pluripotent stem cells (iPSCs) often contain cells of varying grades of pluripotency. We present novel lentiviral vectors targeted to the surface receptor CD30 (CD30-LV) to transfer genes into iPSCs that are truly pluripotent as demonstrated by marker gene expression. We demonstrate that CD30 expression is restricted to SSEA4high cells of human iPSC cultures and a human embryonic stem cell line. When CD30-LV was added to iPSCs during routine cultivation, efficient and exclusive transduction of cells positive for the pluripotency marker Oct-4 was achieved, while retaining their pluripotency. When added during the reprogramming process, CD30-LV solely transduced cells that became fully reprogrammed iPSCs as confirmed by co-expression of endogenous Nanog and the reporter gene. Thus, CD30-LV may serve as novel tool for the selective gene transfer into PSCs with broad applications in basic and therapeutic research.
Gesehen am 21.04.2020